Prevalence and Some Associated Factors of Stunting Among Under-Five Children in Hilla City-Babylon Province, Iraq - Alwan Baiee (Journal of Global Pharma Technology, 2018)
Stunting among children under five years of age is a serious health problem especially in middle and low income countries including Iraq, it is associated with high morbidity and mortality among infants and young children the objective of this study was to identify the prevalence and some correlates of stunting among children under 5 years of age.A cross-sectional descriptive study was conducted, to collect primary information from mothers of 1000 children attending ten randomly selected primary health care centers(five rural and five from city center) in Babylon province- AL-Hilla city during the period from Octobar,2015 through June 2016 a pre tested questionnaire, anthropometric measurements ( length/height for age) were used to assess children's stunting according to -2SD length/ height for age of the World Health Organization Standard Median .The results revealed that the prevalence rate of stunting among 1000 under five children included in this study were 20.6%. Significant statistical associations were found between stunting and the following independent variables; age groups: more in the age group 24>60 months, gender: highly prevalent in boys, maternal education: highly distributed in children with poorly educated mothers, breast feeding: peaked among mixed breast feeders and among children of low family income p<0.05. In conclusion Stunting ( chronic malnutrition) in the study area is still a concern that needs intervention by governmental and non-governmental organizations, improvements in child feeding, and better maternal education are needed to maintain the children's nutritional status to prevent and control this serious health problem .Keywords: Under weight, Stunting, Children. Under-fives, Babylon, Iraq.